Prison overcrowding and ill-treatment: sentence reduction as a reparation measure. A view from Latin America and Europe: Una visión desde América Latina y Europa - Forero Cuellar, Alejandro (Torture Journal, 2023)
The article addresses the issue of prison overcrowding and how it can be declared as a situation constituting ill-treatment or torture under international law. Faced with such a broad phenomenon, the piece focuses on two elements that may help to assess this circumstance: the existence of a minimum standard with respect to living space, and the use of tools to establish the existence of harm caused by inhuman conditions of incarceration. The article will show a novel jurisprudence regarding the decision of some Courts to secure reparation for victims (early release and reduction of sentence time as offsetting) and will address discussion on the scope and limitations of these decisions with the aim of proposing even more courageous measures to ensure group and generalized reparation measures to reduce the rates of structural institutional violence in prisons.